Raka Riki sebagai Ujung Tombak Strategi Komunikasi Pariwisata Dinas Kebudayaan dan Pariwisata Provinsi Jawa Timur - Kurniawan, Helmi; Panuju, Redi (Politeknik Pariwisata NHI Bandung, 2019)
This study aims to determine the communication strategy of the Culture and Tourism Office of East Java Province in utilizing the East Java Raka Raki. The communication strategy analysis by Berlo's SMCR theory (1960) and on the strategic communications approach. Data collection techniques in this research were carried out using field studies (interviews). The research findings show that the formulation of the communication strategy has fulfilled the vision and mission, opportunities and strengths, as well as fulfilling the long-term goals in making use of the East Java Raka Raki. This is supported by the implementation of a communication strategy for the Tourism Industry Sector of East Java Disbudpar with the support of IRARI which is a legal entity. Evaluation of communication strategies in carrying out East Java Raka Raki activities /programs is based on unplanned or unscheduled meetings, meetings are held once every 3 (three) months.